Identifying Herbicides for Use During Zoysiagrass Sprigging - Dani McFadden; Jack D. Fry (Kansas Agricultural Experiment Station Research Reports, 2022)
Weed control after planting warm-season grasses in the spring can be critical for acceptable establishment of the stand. However, many herbicide labels can be unclear on sprigging restrictions before or after the application of a product. Research was conducted on the growth effects of pre- and postemergence herbicides applied at or near the day of ‘Innovation’ zoysiagrass sprigging. Preliminary data from this study shows granular (Ronstar G) and liquid (Ronstar Flo) formulations of oxadiazon caused the least amount of injury to zoysiagrass.
Keywords: turf establishment; weed control